Post-harvest pathogenecity and vivo morphological cahracterization of phytophthora palmivora butler from fruit rot-infected durian (Durio Zibethinus Murray) tested on different hosts - Calalagan, Modassir D. (2010)
In vivo inoculation of Phytophthora palmivora obtained from fruit rot-infected durian and its morphological caharacteristics on different post-harvest fruits/ vegetables were studied. Pathogenicity test was successful on bell pepper (Capsicum annuum), eggplant (Solanum melangena), papaya (Carica papaya), watermelon (Citrullus lanatus) and durian as check. Infection was unsucessful on carrot (Daucus carota), chayote(Sechium edule) cucumber (Cucumis sativus, pomelo (Citrus maxima) and raddish (Raphanus sativus). Marked variability in sporangial shapes and sizes of the pathogenwere onted on the different hosts except on durian suggesting the versatility of P. palmivora to adapt to changes relative to its host. Suggestive of adpatational strategy was the production of chlamydospores bt the pathogen on bell pepper which was not observed on the other hosts. The study recommends care of fruits during harvest, in storage and in transit to avoid infection by the pathogen.